2009
DOI: 10.1002/maco.200805179
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rare earth element Ce and La addition on corrosion behavior of AZ91 magnesium alloy

Abstract: Two types of AZ91 magnesium alloys containing rare earth element Ce or La were fabricated. Hydrogen evolution and electrochemical tests were carried out to evaluate the corrosion behavior of new AZRE (RE ¼ Ce or La) and AZ91 alloys in 3.5% NaCl solutions (pH 6.50). Various corrosion rate tests indicated that addition of RE obviously enhanced corrosion resistance of AZ91 magnesium alloy. The optimal content of RE was 0.92% for Ce and 0.66% for La. Scanning electron microscopy (SEM), energy dispersive spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…Furthermore, the inductive loops of the RE‐modified AZ31 alloys turn back, forming a small capacitive loop in the first quadrant (Figure 6B). This may come from the protective surface film due to the RE addition …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the inductive loops of the RE‐modified AZ31 alloys turn back, forming a small capacitive loop in the first quadrant (Figure 6B). This may come from the protective surface film due to the RE addition …”
Section: Resultsmentioning
confidence: 99%
“…This may come from the protective surface film due to the RE addition. [48][49][50] Figure 6D shows the equivalent circuits for the investigated alloys. The circuit for AZ31 and AZ31-Ca alloys contains the solution resistance (R s ), charge transfer resistance (R t ), constant phase element for the double layer capacitance (CPE dl ), and the inductor for the desorption of intermediates (L).…”
Section: Electrochemical Behaviorsmentioning
confidence: 99%
“…Again, the observations of improved corrosion resistance are explained in similar terms of those described above for AZ91, although in certain cases the grain refinement in the presence of a RE addition leads to a reduction in the size of the alpha-Mg particles. 18 In studies where the influence of the RE alloying addition on corrosion resistance has been investigated systematically, optimum levels are typically within the 0.3 wt% to 1 wt% range, [5][6][8][9][11][12]14 and higher RE compositions are reported to cause increased rates of corrosion. However, in the case of certain individual RE metals such as cerium (Ce) 7 and neodymium (Nd), 17 others have observed significantly higher optimum compositions of 2 wt% and 6 wt%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of work in this area refers to the influence of RE additions on Mg systems that are already heavily alloyed with other metals such as Al and Zn, and there is now a significant body of literature concerning the corrosion properties of AZ91 (9% Al, 1% Zn)-RE alloys. [5][6][7][8][9][10][11][12][13] The beneficial effect of RE additions is typically attributed to grain refinement, 5,[7][8][9][11][12][13] where the presence of RE causes a reduction in both volume fraction and size of betaphase particles. However, other factors also have been proposed, which include the incorporation of RE oxides within corrosion product films formed upon immersion in bulk electrolyte, [6][7][8][9][11][12] giving rise to dense and compact protective surface hydroxide layers.…”
Section: Introductionmentioning
confidence: 99%
“…As elemental addition to Mg-Al, however, it improves corrosion resistance. Liu et al [160] reported a drop in corrosion rate when 0.5 wt % La is added to AZ91 (Figure 31), which they related to a modification of the alloy's microstructure. The formation of needle-like Al-La compounds and the alteration of Mg 17 Al 12 from discontinuous to continuous is observed.…”
Section: Rare Earth (Re) Elementsmentioning
confidence: 99%